Evaluation of Knowledge, Attitudes, and Skills in Evidence-Based Nursing Practice Among Master's Degree Nursing Students. - Abram, Barbara; Radzimska, Oliwia; Janiszewska, Jagoda; Świniarska, Aleksandra; Papierkowska, Roksana; Czapla, Michał; Uchmanowicz, Izabella (Nursing Reports, 2025)
Background: Evidence-Based Nursing Practice (EBNP) plays a crucial role in ensuring high-quality patient care. This study evaluates master's degree nursing students' knowledge, attitudes, and skills related to EBNP, identifying strengths and key gaps that require curriculum improvements to enhance their competencies in evidence-based practice. Methods: A cross-sectional study was conducted among 103 master's degree nursing students at Wrocław Medical University. Data were collected using a demographic questionnaire and the standardized Polish version of the Evidence-Based Practice Profile Questionnaire (EBP2Q). Results: The findings indicate that students demonstrated generally positive attitudes toward EBNP (mean score: 53.43 ± 10.05 out of 70). However, knowledge of research terminology was moderate (44.66 ± 18.01 out of 85), and the frequency of EBNP utilization in practice was relatively low (22.15 ± 8.74 out of 45). Significant differences were observed based on study mode and academic progression, with part-time students scoring higher in attitudes toward competency development (p = 0.02). A weak but positive correlation was found between professional experience and the frequency of EBNP utilization (r = 0.182, p = 0.068), while knowledge of research terminology showed a non-significant association with age (r = 0.167, p = 0.092). Conclusions: These findings highlight the need for targeted curriculum enhancements, particularly in research literacy, practical application opportunities, and the integration of mentorship and educational resources. Strengthening EBNP education will better equip nursing students to implement evidence-based practices in clinical settings, ultimately improving patient care quality.